Evaluation of Learning Outcomes of Dawn Prayer Practice at Baitul Lathif TPA, South Sangatta - Eka Widyanti; Nurwanalianti; Sugianor; Muhammad Yahya Nuzulul Kurniawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to evaluate the effectiveness of learning the practice of Fajr prayer in children at TPA Baitul Latif. The research method used is a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The focus of the evaluation includes children's understanding of the procedures for the Fajr prayer, the ability to carry out prayer movements correctly, and an increase in the discipline of time in carrying out the worship. The results showed that the Fajr prayer practice learning program has had a positive impact on the understanding and skills of TPA children in carrying out worship. However, some challenges were found, such as the lack of motivation of some children and suboptimal family support. Recommendations for further development include improving interactive learning approaches and active involvement of parents in guiding children at home.